(untitled) - Neale, Bill (Harlow, England, 2004)
This new book offers an introduction to financial decision-making, covering key areas of financial management ranging from objectives through to investment financing and dividend policy. The emphasis is on "managing for value" which reflects a growing concern in the focus of modern business management. The book examines business finance from a managerial angle, integrating strategy in a way that has not been achieved yet in most other core finance texts. The material will be relevant to all types of business organisations, and examples are taken from Europe and around the world. Using up-to-date, topical case material, based upon real-life companies familiar to many students, the text analyses value-adding strategies and how practice compares with theory.
Keywords: Business enterprises,Corporations; Finance,Finance